Nano-sized molecularly imprinted polymers for selective detection of Penicillin G - Ismail, Suhainie; Yusof, Nor Azah; Abdul Rahim, Zulaiha; Alang Ahmad, Shahrul Ainliah; Zainuddin, Norhazlin; Abubakar, Lawal; Isha, Azizul; Abd Rahman, Siti Fatimah (Springer, 2026)
Nano-sized molecularly imprinted polymers (NMIPs), synthesized using methacrylic acid and ethylene glycol dimethacrylate, were developed to enhance the recognition and adsorption of penicillin G (PenG) sodium. A noncovalent imprinting approach was employed, wherein the functional monomer methacrylic acid and the crosslinker ethylene glycol dimethacrylate were combined with the PenG template. The pre-polymerization mixture was emulsified via probe sonication into a miniemulsion, yielding PenG–NMIP particles with diameters ranging from 50 to 100 nm. To evaluate this noncovalent imprinting performance, non-imprinted polymers were prepared as controls. The adsorption behavior of the PenG–NMIPs was optimized by systematically investigating the effects of pH, contact time, polymer dosage, and PenG concentration. The maximum binding capacity achieved was 2.56 mg/g, confirming the effectiveness of the imprinting process. The adsorption data were fitted to Langmuir and Freundlich isotherms, with the PenG adsorption process aligning with the Langmuir model. The selectivity of the PenG–NMIPs was further assessed against structurally similar antibiotics—ampicillin and amoxicillin—to evaluate competitive binding. This approach demonstrates promising selectivity and efficiency in the removal of PenG from pharmaceutical formulations, highlighting potential applications of PenG–NMIPs in drug purification and environmental remediation.